SEMANTIC SHIFTS IN LABĪD IBN RABĪʿAH’S POETRY FROM JĀHILIYYAH TO EARLY ISLAM: AL-TAḤAWWULĀT AL-DALĀLIYAH FĪ SYI‘RI LABĪD BIN RABĪ‘AH BAYNA AL-JĀHILIYYAH WA ṢADR AL-ISLĀM - Amanda Rheyna Athaya; Muhsin; Nuur Nuur (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
This study examines semantic shifts in the poetry of Labīd ibn Rabīʿah, a prominent pre-Islamic poet who later embraced Islam, through the lens of Stephen Ullmann’s historical semantic theory. The research aims to investigate how Labīd’s lexical choices reflect the cultural and ideological transition from the Jāhiliyyah period to early Islam. Employing a qualitative descriptive method with a historical-semantic approach, the study analyzes selected verses composed after Labīd’s conversion, integrating semantic and contextual interpretation. The findings reveal multiple types of semantic change, including amelioration, pejoration, broadening, narrowing, and complete semantic shift, indicating a substantial transformation in Labīd’s diction as his worldview evolved from tribal heroism and material values toward faith-based moral principles. Lexical items such as al-anyāb (الأنياب), aswad (أسود), hirāwah (هِراوة), yajūd (يَجود), and al-ḍujūʿ (الضجوع) exemplify how meaning developed in parallel with broader socio-religious change. The novelty of this study lies in its integrated analysis of Labīd’s pre-Islamic and early Islamic lexicon using Ullmann’s framework—an approach rarely employed in previous scholarship—and in its systematic mapping of semantic patterns within an ideological context. This research contributes to historical semantic studies of Arabic poetry by bridging linguistic analysis with cultural and religious transformation.